2014
DOI: 10.1016/j.envexpbot.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Localization and chemical speciation of cadmium in the roots of barley and lettuce

Abstract: Plants have the potential to accumulate toxic amounts of cadmium (Cd), and understanding how and where Cd is stored in plants is important for ensuring food safety.Previous experiments have determined that a greater amount of Cd is translocated into the leaves of lettuce (Lactuca sativa) as compared to barley leaves (Hordeum vulgare).Preferential retention of Cd in root of barley would explain this difference. Hence, the purpose of this study was to determine the localization and coordination environment of Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 39 publications
2
40
0
1
Order By: Relevance
“…The high transfer from soil to roots could be due to the facts that Cd is generally more available in the rhizosphere and uses various pathways of entry including non-specific transporters, Ca 2+ channels, ZIP and IRP transporters (Lux et al, 2011;DalCorso et al, 2013). Inside root tissues, Cd accumulates in the endodermis and in xylem cell walls, or is chelated by phytochelatins that mediated vacuolar storage (Lux et al, 2011;Akhter et al, 2014).…”
Section: Metal Distribution and Accumulation In Miscanthus Organs Andmentioning
confidence: 97%
“…The high transfer from soil to roots could be due to the facts that Cd is generally more available in the rhizosphere and uses various pathways of entry including non-specific transporters, Ca 2+ channels, ZIP and IRP transporters (Lux et al, 2011;DalCorso et al, 2013). Inside root tissues, Cd accumulates in the endodermis and in xylem cell walls, or is chelated by phytochelatins that mediated vacuolar storage (Lux et al, 2011;Akhter et al, 2014).…”
Section: Metal Distribution and Accumulation In Miscanthus Organs Andmentioning
confidence: 97%
“…A recent study by Xin et al (2013) who investigated the role of roots in Cd accumulation in two water spinach cultivars using reciprocal grafting is an elegant example of the application of the technique. Current research has shown differential root-to-shoot regulation of photosynthetic proteins, sulphur and glutathione metabolism involved in signaling and secondary metabolism in Cd hyperaccumulation (Akhter et al 2014;DalCorso et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…S1). Such result is reminiscent of Cd speciation studies in the roots of barley and lettuce , showing that most of cadmium ions were bound to ligands containing SO42.…”
Section: Resultsmentioning
confidence: 70%
“…In the present study, however, a fairly good correlation was found between Cd and SO42 in superphosphate, NPK‐fertilizers, urea phosphate, and potassium phosphate. The substitution of Ca with Cd results from a Cd 2+ ionic radius (0.109 nm) similar to that of Ca 2+ (0.114 nm), thus, leading to a CdP or CdS bond and the formation of Cd 3 (PO 4 ) 2 and/or CdSO 4 within the fertilizers . The relationship between Cd and sulfate is conditioned to the presence of high sulfate contents in the NPK group of higher pH (Supporting Information Tab.…”
Section: Resultsmentioning
confidence: 99%